SEX AND SEXUALLY TRANSMITTED INFECTIONS: EXPERIENCES OF MALE STREET YOUTH IN MEDAN, INDONESIA - Augustina Situmorang (Research Centre for Population, Indonesian Institute of Sciences, 2006)
Street youth all over the world have been identified as the group suffering most from Sexually Transmitted Infections (STis) including HIV/AIDS. Nevertheless as they are very difficult to reach, this group has remained an underserved population. Based on a survey of 53 male street youth aged 15-24 years, seven open-ended interviews and one FGD, this study aims to explore sexual lives and risk of sexually transmitted infections including HIV infection among street youth in Medan. These include their views and experiences of sex, pornography, condom use and STis including HIV/AIDS. The study found that two thirds of respondents are sexually active and the majority of them reported having had sex with prostitutes. Openended interviews and FGD revealed that none of respondents use condom consistently. Many of them had been infected with STis, which they cured themselves.Keywords: Street youth, Sex. STis and HIV I AIDS, Medan, Indonesia.